Considering Role of Probiotic on Respiratory Disease: Is Probiotic Possible to Treat COVID-19? - Eighty Mardiyan Kurniawati; Nur Anisah Rahmawati; Anna SurgeanVeterini (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: COVID-19 is a new variant of the corona virus known as a pandemic disease. The numberof cases has increased every day around the world. Unfortunately, treatment in management has not beensatisfactory.Purpose: This study aims to examine the role of probiotics in respiratory disease and the possibility ofmanaging COVID-19 through an analysis of its function.Method: This study is a review. Quality journals until 2020 were searched in the Pubmed database forthe keywords ‘respiratory’ or ‘asthma’ or ‘pneumonia’ or ‘lung’ or ‘influenza’ and ‘COVID-19’. Compileddata includesthe author, type of study, type of probiotic, duration of intervention, target population, results,conclusion and side effects that occurredResults: We analyzed 9 experimental studies. Some studies related to respiratory disorders used theLactobacillus Sp as probiotic. One research used Fructooligosacharide as additional ingredient. The researchuse different doses and timing of interventions 14 days - 6 months. The diseases covered in this reportare asthma, pneumonia, and influenza. Probiotics can reduce symptomps, duration in hospitality risk, andquality of life.Conclusion: The ability of probiotics in the management of respiratory diseases provides hope for themanagement of COVID-19, of course, it is balanced with further research that is able to analyze cleardosages, types and roles.